Efficacy and safety of controlled ovarian stimulation using GnRH antagonist protocols for emergency fertility preservation in young women with breast cancer—a prospective nationwide Swedish multicenter study - Marklund, Anna (Hum Reprod, 2020)
STUDY QUESTION: How efficacious and safe are the current approaches to controlled ovarian stimulation (COS) aimed at fertility preservation (FP) in women with breast cancer (BC)? SUMMARY ANSWER: In women with BC undergoing COS aiming at egg/embryo cryopreservation, letrozole-based protocols and those randomly started were equally effective compared with conventional COS, and the overall survival was similar between the women that proceeded to FP and those who did not. WHAT IS KNOWN ALREADY: Cryopreservation of oocytes and embryos is an established method for FP in women with BC. Recent improvements to COS protocols include concomitant use of letrozole, random-cycle start day of stimulation and the use of GnRHa for the egg maturation trigger. To date, limited sample size of the available studies has not allowed investigation of differences in the efficacy of the different approaches to COS for FP in this patient population. STUDY DESIGN, SIZE, DURATION: A prospective multicenter study with national coverage including 610 women with BC counseled between 1 January 1995 and 30 June 2017 at six Swedish FP regional programs. PARTICIPANTS/MATERIALS, SETTING, METHODS: After counseling, 401 women elected to undergo COS. Treatments differed in the use or not of concomitant letrozole, a conventional or random-cycle day COS initiation and the use of hCG versus GnRHa trigger for oocyte maturation. Numbers of cryopreserved oocytes and embryos were defined as primary outcome. Pregnancy attempts, reproductive outcomes and long-term survival, investigated by the linking of individuals of the cohort to the total population register of the Swedish Tax Agency (up to 25 November 2018), were evaluated. MAIN RESULTS AND THE ROLE OF CHANCE: Using letrozole or not resulted in similar numbers of oocytes and embryos cryopreserved (mean(oocytes) = 9.7 versus 10 and mean(embryos) 4.0 versus 5.3, respectively), similar to COS with random versus conventional start (mean(oocytes) 9.0 versus 10.6 and mean(embryos) 4.8 versus 4.8). In COS with letrozole, a GnRHa trigger was associated with a higher number of oocytes retrieved (P < 0.05) and embryos cryopreserved (P < 0.005), compared with conventional hCG trigger. Of 99 women who returned to fertility clinics after cancer treatment, 32 proceeded to thawing of oocytes or embryos and 10 of them had live births. The all-cause survival between the women that underwent COS and those who did not was similar and did not differ between the two groups. LIMITATIONS, REASONS FOR CAUTION: Data on tumor characteristics and estrogen receptor (ER) status were not known for all women at the time of FP counseling and planning of COS, thus protocols with letrozole have been used for both estrogen-sensitive and non-estrogen-sensitive BC. For the same reason, subsequent adjustment for ERs in the BC or tumor characteristics as potential confounders were not performed as these parameters were not available and did not influence the provision of FP through COS. WIDER IMPLICATIONS OF THE FINDINGS: The results of our study support the premise that recently introduced potential improvements to COS protocols for FP in women with BC are efficacious and safe. STUDY FUNDING/COMPETING INTEREST(S): This study was supported by research grants from the Swedish Cancer Society, the Stockholm County Council, the Percy Falk Stiftelsen, Radiumhemmets Forskningsfonder, The Swedish Breast Cancer Association and Karolinska Institutet to K.A.R.W. J.B. reports grants from Amgen, AstraZeneca, Pfizer, Roche, Sanofi-Aventis and Merck, outside the submitted work, and payment from UpToDate to Asklepios Medicine HB for a chapter on BC prediction and prognostication. All the other authors have no competing interests to report.